BARRIERS FACED BY WOMEN OF REPRODUCTIVE AGE IN SEEKING CERVICAL CANCER SCREENING SERVICES IN KATABI MILITARY HOSPITAL, WAKISO DISTRICT. A CROSS-SECTIONAL STUDY. - Lusike, Joan; Kyere, Olivia; Nalubega, Jane Frank; Naggulu, Immaculate Prosperia (Student’s Journal of Health Research Africa, 2025)
Background Cervical cancer (CC) is one of the most common cancers among women of reproductive age in low- and middle-income countries. The study aims to assess the barriers faced by women of reproductive age in seeking cervical cancer screening services in Katabi Miltary Hospital, Wakiso. Methodology The study adopted a descriptive design using quantitative approach. This design was suggested to enable the researcher to capture information of respondents views in own words. Processed data was analyzed by grouping the same ideas together and interpreted. Finally, data was presented in form of graphs, tables, and pie chart. Results The majority of the respondents, 63.3%, reported that there were some social beliefs such as “not everyone should see a female’s genitalia, more so men if not their partners”. 45.0%, suggested fear of the results, (70.0%) of the respondents couldn’t afford the screening, 55.6% reported having fear towards CC screening, Socioeconomic findings 41.6% wouldn’t seek CC screening due to poverty, 65.0%) reported that the clinic hours were not convenient for them and 53.4% reported long waiting hours as one the other facility based barriers, 33.3% of them reported health workers having poor attitude while providing these services. The majority of the participants (58.3%) were Baganda by tribe. Conclusion The barriers faced by women of reproductive age in seeking cervical cancer screening services were the cost of screening services, inconvenient clinic hours, prolonged waiting hours, fear, and poor attitude of health workers. Recommendations. To the ministry, the government and other stakeholders such as NGOs, should establish more health facilities and equip them with supplies for cervical cancer screening so as to further avail services to its female citizens.